Studies on mechanical property of squeeze cast and heat treated AA6061-ZrO2 composite - A Raja Annamalai; Johny James; P Kuppan; S Hemakumar; Chun-Ping Jen (Materials Research Express, 2020)
This work deals with processing, characterization, and study of the mechanical property of AA6061-ZrO _2 composite by stir casting unit combined with squeeze casting setup. Morphology study of the refined composite was measured with the help of Optical Microscope and Scanning Electron Microscopy (SEM). The Energy Dispersive x-ray spectroscopy was performed to observe the desirable elements present in the processed composite. The EDX investigation endorses the presence of Aluminum, Zirconium, and Oxygen, are the elements of the desirability. The processed composite displayed increased hardness value when related to the base aluminum alloy AA6061 at test conditions. The tensile tests have been performed for the refined specimen both in cast and heat treated conditions. 20%–63% improvement in tensile strength as an outcome of the inclusion of ZrO _2 particles and heat treatment process was recorded, and the fashion was analyzed. Finally, all the three composite specimens were tested for wear resistance property for the support of pin on disc wear test kit. The wear trend due to the addition of ZrO _2 particles was discussed in a detailed manner.